The role of usability, usefulness and frame in persuasive health communication - Leaviss, Joanna (2010)
Background: A large proportion of ill-health is preventable (Signorelli 1993). A goal for health promoters is to provide information about health risks with the aim of persuading individuals to modify their behaviour. Previous research suggests that the readability of many health promotion materials is too low for effective comprehension. Evidence suggests that much of the health information available is written at a level that is too difficult for the target populations (e.g. Dollahite et al. 1996, Meade & Byrd 1989, Greenfield et al. 2005). Whilst this work is useful in identifying barriers to accessibility to health information, there has been little research that systematically explores the concept of usability within the context of health information.